Continuity Pattern Structure of Target Scene in Support of Multiple-Channel ISAR Imagery - Wang, Jingjing; Liu, Meiru; Zhang, Hang; Han, Shengliang; Zhang, Liren (IEEE access, 2019)
This paper presents a multiple-channel ISAR system for multiple air-targets imaging by illuminating a sequence of N narrow and high-gain signal beams over a wide area. Echoes are received by M channels and synthesized into N independent sub-channels using space-time processing technique. The ISAR imaging for each sub-channel is based on the continuity pattern structure technique. Comparing to the conventional ISAR imaging methods, the proposed method can reduce the computational complexity. The numerical results obtained from simulation and experiments demonstrate that the proposed multiple-channel ISAR system has the advantage in detecting multiple air-targets over a wide area and preserving the weak scatterer points comparing to conventional ISAR system.